1996
DOI: 10.1091/mbc.7.7.1059
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of the Drosophila HRB87F/hrp36 hnRNP protein have limited effects on alternative splicing in vivo.

Abstract: The Drosophila melanogaster genes Hrb87F and Hrb98DE encode the fly proteins HRB87F and HRB98DE (also known as hrp36 and hrp38, respectively) that are most similar in sequence and function to mammalian A/B-type hnRNP proteins. Using overexpression and deletion mutants of Hrb87F, we have tested the hypothesis that the ratio of A/B hnRNP proteins to SR family proteins modulates certain types of alternative splice-site selection. In flies in which HRB87F/hrp36 had been overexpressed 10- to 15-fold above normal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 77 publications
(114 reference statements)
2
41
0
Order By: Relevance
“…As Dscam is essential for viability 5 , it is surprising that flies lacking hrp36 are viable 25,26 and that exon 6 splicing occurs normally in hrp36-null flies (S.O. and B.R.G., unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…As Dscam is essential for viability 5 , it is surprising that flies lacking hrp36 are viable 25,26 and that exon 6 splicing occurs normally in hrp36-null flies (S.O. and B.R.G., unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of RRM1 and RRM2 cluster in two separate groupings with bootstrap confidence intervals of 85% and 95%+ The RRM1 sequences are somewhat more tightly conserved (.60% identity with human A1) than are the RRM2 sequences (.48% identity)+ Strikingly, the patterns of branching for RRM1 and RRM2 sequences are almost identical, except for the placement of the branch representing the minor human variant hnRNP A0 (Myer & Steitz, 1995)+ Further analysis of the sequence of hnRNP A0, including sequences at the C-terminal domain (data not shown) and the IRL (Fig+ 6B), indicates that this protein groups most closely with the other vertebrate sequences, as observed in the branching for the more highly conserved RRM1 sequences+ The nearly identical pattern of branching for RRM1 and RRM2 strongly suggests that the two RRMs have evolved in parallel+ Aside from two divergent proteins, hnRNP A0 (Myer & Steitz, 1995) and the Caenorhabditis elegans protein (Iwasaki et al+, 1992), whose RRMs show 50-69% identity to those of human hnRNP A1, the hnRNP A1-like proteins cluster into two groups representing insect and vertebrate proteins+ The division of insect and vertebrate RRM sequences on two separate branches most likely represents independent duplications of an ancestral hnRNP A1-like protein, because each of the insect proteins is almost equally distant from each of the vertebrate proteins+ The two Drosophila proteins are functionally similar to human A1: overexpression of Hrb87F and Hrb98DE has been shown to promote exon skipping in vivo (Shen et al+, 1995;Zu et al+, 1996), an effect that may involve preferential use of distal splice sites+…”
Section: Phylogenetic Analysis Of Hnrnp A1-like Proteinsmentioning
confidence: 99%
“…We have shown previously that overexpression of either HRB87F/hrp36 or HRB98DE/hrp38 in flies is able to induce an aberrant exon-skipping pattern in the endogenous pre-mRNA encoding dopa-decarboxylase (Ddc), in which both of two short internal exons are skipped (Shen et al+, 1995;Zu et al+, 1996) (see Fig+ 2A)+ Although this particular alternative splicing activity is not a biologically relevant function of HRB87F/ hrp36 (Zu et al+, 1996), the endogenous Ddc splicing FIGURE 1. HRB87F/hrp36 protein mutants and their stable expression in flies+ A: Schematic of the wild-type and mutant HRB87F/ hrp36 proteins used in this study+ The three-domain structure consists of two RNA-binding domains (RBDs) and one glycine-rich domain (GRD)+ Six versions of the gene were transformed into flies, all under the control of the hsp70 promoter and all tagged at their N terminus with the Flag epitope+ The "X" within an RBD denotes two amino acid changes (phe r asp) within the conserved RNP-1 octamer motif+ Specifically, for RBD-1, the sequence RGFGFITY was changed to RGDGDITY+ For RBD-2, the sequence RGFAFIEF was changed to RGDADIEF+ In addition to these RBD sequence changes, other mutant proteins had the GRD deleted or the GRD substituted by the RS domain from the Drosophila B52 protein (see Materials and Methods)+ The nomenclature used for these proteins is shown at the left+ B: Western blot analysis of HRB87F/hrp36 proteins+ Total larval proteins from the six homozygous transformed fly strains were isolated either before or 8 h after heat-shock induction of the transgene, and were probed with anti-Flag Ab after electrophoresis+ The position of molecular weight standards is shown on the left+ Flag-tagged proteins of the expected size (indicated by asterisks on the right side) were induced in each case and were stable up to 8 h after induction+ The last two lanes (R1-R2-RS) were done at a different time but under exactly the same conditions+ This strain consistently showed a certain level of basal expression of flag-tagged proteins, presumably because of genomic site of insertion of the P element+ All experiments were done after hs induction when a protein of the expected size is the major product+ assay remains convenient for determining hnRNP protein domains involved in protein-protein and/or protein-RNA interactions+ The RT-PCR analysis in Figure 2B was done in flies homozygous for the various wild-type and mutant inducible transgenes+ Larval hypodermal tissue was used, and thus the ACD splice form of Ddc mRNA is expected, in which the B exon is skipped (Fig+ 2A)+ The analyses were done 8 h after induction of these transgenes to avoid possible heat-shock effects on splicing+ When overexpressed, the wild-type hnRNP protein induced exon skipping as seen previously (ACD to AD form in Fig+ 2B, lane 2) (Zu et al+, 1996), whereas none of the mutant proteins had any effect (Fig+ 2B, lanes 3-12)+ Thus all three of the domains are involved in this activity, as was shown previously for human hnRNP A1 in vitro (Mayeda et al+, 1994)+ In a second experiment, heterozygous flies were made that were capable of overexpressing two different transgenes at the same time+ The wild-type HRB87F/hrp36 protein was overexpressed along with one of the mutant proteins to test for possible transdominant suppression effects on the exon-skipping activity (Fig+ 2C)+ Surprisingly, none of the mutant proteins suppressed the effect, but two of the mutant proteins (R1-X-G and R1-R2-RS) enhanced the exon-skipping activity provided by one copy of the wild-type transgene (Fig+ 2C, lanes 5 and 7) similar to a second copy of the wildtype transgene (lane 3)+ Thus, although a double-ov...…”
Section: Stable Overexpression Of Wild-type and Mutant Hrb87f/hrp36 Pmentioning
confidence: 99%
“…We analyzed the pattern of binding of wild-type and mutant HRB87F/hrp36 proteins to sites of transcription on polytene chromosomes+ Previous studies have established that the protein has a wide distribution pattern during normal growth conditions (Amero et al+, 1992;Matunis et al+, 1993), but a single strong site of accumulation (on heat-shock puff 93D) immediately after heat shock (Dangli et al+, 1983;Hovemann et al+, 1991;Zu et al+, 1996)+ These two chromosomal staining patterns are shown for our epitope-tagged wild-type HRB87F/hrp36 protein in Figures 4A (heat shock) and 5A (normal growth)+ We asked which domains of the protein are responsible for these two very different native RNA binding patterns+…”
Section: Rbd-2 and The Grd Reproduce The Distribution Pattern Of The mentioning
confidence: 99%
See 1 more Smart Citation